Cross-national comparison of job types: analysis using the EU LFS and Albanian LFS - Elvisa Drishti (Global Labor Organization (GLO), 2021)
This paper is dedicated to the cross-national comparison of the labour markets of the EU member countries and Albania. The aim is to establish whether or not cross-national variations in propensities of being hired in a non-standard job are the result of differences in national institutional regimes and labour market regulations. An adapted version of the Fraser Index is used to explain cross-country differences in relation to the application of rigid labour market regulation. The econometric analyses indicate that the net effect of more stringent labour market regulation, increase job quality in different senses: in less affluent transition economies, more workers use involuntary non-standard jobs as a means to escape unemployment. On the other hand, in affluent economies, interventionist policies are associated with high levels of voluntary non-standard work and low unemployment.
Keywords: 330; involuntary non-standard employment; Albania; European Union; labour market regulation; post-communist